Efeitos da comunicação alternativa na interação professor-aluno com paralisia cerebral não-falante - Silva, Rafael Luiz Morais Da; Silva, Simone Souza Da Costa; Pontes, Fernando Augusto Ramos; Oliveira, Ana Irene Alves De; Deliberato, Débora [UNESP] (Associação Brasileira de Pesquisadores em Educação Especial - ABPEE, 2013)
Speech has been regarded as a social communicative modality required for building relationships in different contexts and cultures. Nevertheless, this is not always a readily available resource, especially for those who have developmental disorders. In this sense, Augmentative and Alternative Communication resources and strategies have been used by nonspeaking students with disabilities as useful tools to achieve greater social participation in different environments. Therefore, the present study examined the interaction between teachers and a student with cerebral palsy before and after the use of Alternative Communication strategies in the classroom. The study had a quantitative and qualitative nature and was designed as an intervention study. There were four main stages: 1) filming before the introduction of the resources in the classroom, 2) training the school teachers 3) providing technical assistance regarding the use of alternative communication to the child's teacher 4) filming teacher-student interactions using these technological resources. The interactions were transcribed and grouped into links. In this research, a link means the initiator's behavior directed to the exchange partner and the response in sequence from the interlocutor back to the initiator. It was found that the established interactions presented a maximum of four links, with greater frequency for episodes of 1st and 2nd links. After the intervention, there were different contexts with the presence of interactions up to the 6th link, often greater frequency for episodes of 1st, 2nd and 3rd links. In addition, the teacher showed a tendency to use symbols only as a tool for evaluating and teaching concepts. This perception changed as the teacher became familiarized with the Augmentative and Alternative Communication technology resources.

A fala tem sido vista como modalidade comunicativa socialmente exigida para a construção de relações em diferentes contextos e culturas. Entretanto, essa nem sempre é o recurso mais disponível principalmente para aqueles que apresentam alterações no seu desenvolvimento. Nesse sentido, os recursos e estratégias de Comunicação Alternativa são utilizados como ferramentas úteis para que o aluno com deficiência não-falante possa alcançar maior participação social nos diversos ambientes. Por isso, a presente pesquisa analisou a interação professor-aluno com paralisia cerebral antes e após o uso de estratégias e recursos de comunicação alternativa em sala de aula comum. Realizou-se estudo de caráter quanti-qualitativo, do tipo estudo de caso com pesquisa-intervenção. Foram realizadas quatro etapas principais: 1) filmagens antes da introdução desses recursos em sala de aula; 2) capacitação dos professores na escola e; 3) assessoria técnica ao professor para o uso da comunicação alternativa e; 4) filmagens dos episódios interativos com o uso dessas tecnologias. As interações foram transcritas e agrupadas em elos. Nessa pesquisa, um elo compreendeu o comportamento do iniciador dirigido ao interlocutor e a resposta sequencial deste ao iniciador. Verificou-se que as interações estabelecidas apresentavam no máximo quatro elos, com maior frequência para episódios de 1º e 2º elos. Após a intervenção, observou-se cenário diferenciado com a presença de interações de até 6º elo, com freqüência maior para episódios de 1º, 2º e 3º elos. Além disso, a professora manifestou tendência para utilizar os símbolos apenas como ferramenta de avaliação e ensino de conceitos, percepção essa que se transformou a medida que essa se apropriava das tecnologias de comunicação alternativa.
The effects of alternative communication in the interactions between a teacher and a nonspeaking student with cerebral palsy
Keywords: Educação Especial; Interação professor-aluno; Sistemas de comunicação; Paralisia cerebral; Special education; Student-teacher Interaction; Communication System; Cerebral Palsy